Pengaruh Pengendalian Diri (Self-Control) dan Minat Belajar Ekonomi Terhadap Hasil Belajar Mata Pelajaran Ekonomi Siswa Kelas XII IPS SMA Negeri 4 Singaraja - Jawak, Iklasni Rohayani; Meitriana, Made Ary (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This study aims to determine the influence of self-control and interest in learning economics on the learning outcomes of economics students in grade XII IPS SMA Negeri 4 Singaraja. The type of research used in causal research and the type of data used use a quantitative approach. The data collection techniques used in the study used questionnaire and documentation methods. The sample used was 89 respondents. The sampling technique used is proportional random sampling. The data analysis techniques used in the study were multiple linear regression analysis, classical assumption test, t hypothesis test, F hypothesis test, and determination coefficient. The results of the study showed that (1) self-control had a significant positive effect on learning outcomes, (2) learning interest had a positive effect on learning outcomes, and (3) the influence of self-control and learning interest had a significant positive effect on learning outcomes. This can be seen from the results of multiple linear regression with an X1 value of 0.461 and an X2 value of 0.611. The results of the t-test of the self-control variable have a significant value of 0.001 less than 0.05, which means that H1 is accepted, and the results of the t-test of the learning interest variable have a significance value of 0.000 less than 0.05, which means that H2 is accepted, and the result of the F test has a significance value of 0.000 less than 0.05, which means that H3 is accepted.